Improved ferroelectric and piezoelectric properties and structural correlations in a new ceramic 0.38Ba(Cu1/3Nb2/3)O3–0.62PbTiO3 by MnO2 additive - Prajapati K.; Singh A.K. (My University, 2025)
The tailoring effects of MnO2 additive on 0.38Ba(Cu1/3Nb2/3)O3–0.62PbTiO3 ceramic have been investigated for structure, dielectric, ferroelectric and piezoelectric properties. XRD, XPS, SEM and EDS techniques have been used to characterize the compositional controlling of different structures and the chemistry of the resulting phases. The MnO2 addition has been found very effective in improving the piezoelectric, dielectric and ferroelectric properties and modifying the crystal structure and microstructure of the parent compound. The Rietveld refinement reveals that the 0.38Ba(Cu1/3Nb2/3)O3–0.62PbTiO3 ceramic has a rare crystal structure with two coexisting tetragonal phases whose tetragonalities and phase fractions transform with the increasing concentration of MnO2 additive. The tetragonal phase of both the end components is retained in this solid solution composition with modified lattice distortion. A small amount of MnO2 additive in the ceramic, typically 1 wt%, gives maximum enhancement of piezoelectric response. A profound correlation between the structure and physical properties has been established for defect-engineered ceramics. Graphical abstract: (a)XRD pattern of 0.38Ba(Cu1/3Nb2/3)O3–0.62PbTiO3 ceramic for varying MnO2 additive content. Inset—Zoom view of XRD pattern for illustration of (200) reflection.(b)Variation of d33 with varying MnO2 additive content for 0.38Ba(Cu1/3Nb2/3)O3–0.62PbTiO3 ceramic.(c)P–E hysteresis loop of 0.38Ba(Cu1/3Nb2/3)O3–0.62PbTiO3 ceramic for varying MnO2 additive content.[Figure not available: see fulltext.] © 2023, The Author(s), under exclusive licence to The Materials Research Society.